Grinding Effect of Rotation Speed on the Surface Changes of Multi-Walled Carbon Nanotubes and Their Dispersion Ability - Munkhbayar, B.; Bat-Erdene, Munkhjargal; Choi, Byeongdae; Joung, Taewhee; Chung, Hanshik; Jeong, Hyomin (Asian Journal of Chemistry, 2012)
The present work provides basic insight to largely improving the dispersion of treated multi-walled carbon nanotubes in aqueous solution with grinding and ultrasonication. The present study consists of dry and wet grinding of multi-walled carbon nanotubes with rotation speeds of 200, 300, 400 and 500 rpm and both type of grinding with highest rotation speeds assisted to ultra-sonication dispersion of multi-walled carbon nanotubes in aqueous solutions. A simple method of purifying process also has been discussed in this study. The results demonstrate the grinding method has urgent advantage for dispersion of multi-walled carbon nanotubes in aqueous solution: grinding can break up large multi-walled carbon nanotube aggregates into a number of small aggregates along with exfoliation to individual nanotubes which can easy the work loading of ultrasonication for dispersing multi-walled carbon nanotubes.